Spatially-varying multi-degree-of-freedom electromagnetic energy harvesting - Gatti, Rathishchandra Ramachandra (Curtin University, 2013)
This work presents the theoretical modelling of a novel spatially varying multi-degree of freedom electromagnetic vibration energy harvester(EMVEH) that integrates two novel strategies of energy harvesting - the spatial variation of the magnetic field and the design of multi-degree of freedom energy harvesters thus making a very versatile electromagnetic energy harvester model. The EMVEH models were theoretically formulated using analytical and numerical simulation and then followed by experimental validation.